An empirical investigation of ringgit Malaysia - Low, Shu Fang (2015)
This study investigates factors that influence the Malaysian exchange rate using quarterly data from 1996Q1 to 2015Q2. The Johansen-Juselius cointegration test is used to assess the long run equilibrium relationship between the Malaysian exchange rate, government consumption, trade openness and net foreign assets. The long run VECM results indicate that the government consumption, the trade openness and the net foreign assets are the factors that significantly influence the Malaysian exchange rate. The government consumption and the trade openness have negative relationships with the Malaysian exchange rate, while the net foreign assets is found to have a positive influence on the Malaysian exchange rate. This study provides insights for the policy maker to justify the factors that influence the exchange rate and use the factors as a channel to influence the Malaysian exchange rate. Results of this study enhance existing limited knowledge of the exchange rate study using the BEER model in determining factors that influence the Malaysian exchange rate, and the period of study covers a number of situation where the Malaysian exchange rate had a significant drop in value.